Introduction to the Special Issue on Improving Early Childhood Nurturing Care to Support Childhood Development and Adult Health - Hermano Alexandre Lima Rocha (MDPI AG, 2023)
Background: Child development is an ongoing process that occurs from birth to adolescence and is shaped by various factors, such as genetics, the environment, and experiences [...]